2018
DOI: 10.1134/s1990341318020049
|View full text |Cite
|
Sign up to set email alerts
|

Globular Clusters: Absolute Proper Motions and Galactic Orbits

Abstract: We cross-match objects from several different astronomical catalogs to determine the absolute proper proper motions of stars within the 30-arcmin radius fields of 115 Milky-Way globular clusters with the accuracy of 1-2 mas/yr. The proper motions are based on positional data recovered from the USNO-B1, 2MASS, URAT1, ALLWISE, UCAC5, and GAIA DR1 surveys with up to 10 positions spanning an epoch difference of up to ∼ 65 years, and reduced to GAIA DR1 TGAS frame using UCAC5 as the reference catalog. Cluster membe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Located at R = 8.7 kpc, it is an old (≈ 12.50 Gyr, Dotter et al 2010) GC that lies at a region of low foreground interstellar reddening, with E(B −V ) = 0.063 mag (Lee et al 2014, hereafter L14), making it an excellent candidate for the study of GCs in the densest regions of the Milky Way. It has been frequently assumed to belong to the Bulge due to its proximity to it at about R GC ≈ 2.6 kpc, however its dynamics point out to a inner Halo membership since the work of Dinescu et al (2003), a conclusion now confirmed by brand new proper motion estimates from Gaia 1 (Vasiliev 2018;Chemel et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…Located at R = 8.7 kpc, it is an old (≈ 12.50 Gyr, Dotter et al 2010) GC that lies at a region of low foreground interstellar reddening, with E(B −V ) = 0.063 mag (Lee et al 2014, hereafter L14), making it an excellent candidate for the study of GCs in the densest regions of the Milky Way. It has been frequently assumed to belong to the Bulge due to its proximity to it at about R GC ≈ 2.6 kpc, however its dynamics point out to a inner Halo membership since the work of Dinescu et al (2003), a conclusion now confirmed by brand new proper motion estimates from Gaia 1 (Vasiliev 2018;Chemel et al 2018).…”
Section: Introductionmentioning
confidence: 95%
“…More recently, Pérez-Villegas et al (2018) analyzed 9 bulge GCs and concluded that they move on rather eccentric prograde or retrograde orbits that are strongly influenced by the Galactic bar. A chaotization of the cluster orbits due to the MW bar was also found by Chemel et al (2018) from the analysis of the motions of 115 GCs in a non-axisymmetric MW potential with a bar.…”
Section: Introductionmentioning
confidence: 53%
“…Differences in the abundances of α-elements in the stellar objects of the Galaxy and the surrounding low-mass dwarf satellite galaxies confirm the wellknown conclusion that all globular clusters and field stars of the accreted halo are remnants of galaxies of higher mass than the current environment of the Galaxy. A possible exception is a distant low-metal cluster with low relative abundance of α-elements Rup 106. stars and dwarf satellite galaxies, which we use for comparison.For all 157 globular clusters, we calculated the rectangular coordinates from positions and distances from [7], and for 115 of them-from [8]. We supplemented the data for the last 115 clusters with cylindrical velocity components, taking them from the authors of [8], and for the clusters Ter 4, Pal 3, Pal 5, Pal 13, NGC6528 and NGC7006 calculated them from their proper motions, radial velocities and distances from [7].…”
mentioning
confidence: 99%
“…A possible exception is a distant low-metal cluster with low relative abundance of α-elements Rup 106. stars and dwarf satellite galaxies, which we use for comparison.For all 157 globular clusters, we calculated the rectangular coordinates from positions and distances from [7], and for 115 of them-from [8]. We supplemented the data for the last 115 clusters with cylindrical velocity components, taking them from the authors of [8], and for the clusters Ter 4, Pal 3, Pal 5, Pal 13, NGC6528 and NGC7006 calculated them from their proper motions, radial velocities and distances from [7]. As a result, the number of clusters with known velocities increased by more than two-thirds compared to our previous work MKG19 and totals 121 objects.…”
mentioning
confidence: 99%
See 1 more Smart Citation